PENGARUH PERUBAHAN JUMLAH PENDUDUK TERHADAP KUALITAS AIR DI INDONESIA - Nur Afiyah Maizunati; Mohamad Zaenal Arifin (Badan Perencanaan Pembangunan, Penelitian dan Pengembangan Daerah Provinsi Jawa Tengah, 2017)
Ongoing population growth and urbanization can cause pressure on water systems, especially in urban areas. Several previous studies have found evidence of an influence between population and water quality. However, the phenomenon in Indonesia is slightly different, because although population growth has decreased trend, but the acquisition of water quality index still fluctuate in several years. This study aims to determine the significance influence of population on water quality in Indonesia. Data analysis is done through regression of panel data of 33 provinces with fixed effect model, The results showed that the population has a negative influence on water quality in Indonesia. An increase on population by 1,000 people tends to lower the water quality index by an average of 1.13 points (cateris paribus). Population growth control becomes absolute and priority in Indonesia. However, these efforts need to be accompanied by continuous improvement of competence and welfare, so that the social awareness and economic capacity of each population are increased in order to achieve a better maintenance on the quality of the environment.